การประยุกต์ใช้กราฟอัลกอริทึมสำหรับกราฟทางเคมี - พิมลนาฏ สุนเทียน (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The topic of research is "Application of graph algorithm for chemical graph". The objectives of this research are to find chemical graph from chemical formula, find chemical formula from chemical graph, check isomerism of 2 chemical graph, find maximum sub graph of 2 chemical graph and find monomer from polymer by creating program which use knowledge about Chemistry Mathematics and Graph Algorithm. The testing result of the program show the program can be used efficiently.